Determination of O-containing functional groups distribution in low-rank coals by chemical titration - Zhou, J.; Wang, Y.; Huang, X.; Zhang, Shu; Lin, X. (2013)
Distribution of oxygen-functional groups (carboxyl, alcohol-hydroxyl, phenol-hydroxyl, methoxyl and carbonyl) in 4 Chinese low-rank coals was evaluated based on chemical analysis. Concentration of carboxyl was quantitated by acetic acid calcium ion exchange method and the buffer (pH=8.3). The effect of analysis condition on the concentration of carboxyl and total acidity was studied. The results show that the reliable results are obtained in N 2 atmosphere other than in air. The occurrence of carboxyl in coal is carboxylate. When quantitating the concentration of phenol-hydroxyl in the acid-washing brown coal with ion exchanged method, its concentration increases with increasing pH value. Concentration of carboxyl and hydroxyl account for 34.49% and 34.79%, respectively, in the total oxygen for the dry ash free basis brown coal. Different concentrations of carbonyl exist in the low-rank coals, but that of methoxyl is little.